VR for Ocean Health Awareness ... - Bailenson, Jeremy; Queiroz, Anna C. M. (OSF Registries, 2022)
This study will compare the effects of VR for Ocean Acidification Awareness and learning to traditional lectures and videos with middle and high school students. Participants will learn about the human activities’ impacts on Ocean Acidification and its consequences on marine biodiversity. We will measure learning, learning autonomy, learning agency, self-efficacy, and environmental awareness before and after the intervention. ...